Embedded in context: How time and distance affect the convergence of personnel selection practices - Torsten Biemann; Wolfgang Mayrhofer; Irmela Koch-Bayram (Human Resource Management Journal, 2023)
The debate on convergence versus divergence or stasis in human resource management (HRM) practices over time is still ongoing. We look at configurations of organisations' personnel selection practices and empirically analyse the role of geographic, cultural and regulatory institutional distance between countries for emerging similarity or dissimilarity in these practices. We also examine whether convergence occurred between 1995 and 2015. Based on the Cranet data of 25,869 organisations from 42 countries and statistical tests using energy distance, we find a pattern over time, moving from stasis to divergence. In addition, personnel selection configurations relate to cultural and regulatory institutional differences in the sense that smaller distances lead to higher similarity. This is not the case, however, for geographic distance. Our study adds to the debate on HRM convergence and offers a new method of analysis for other areas of HRM research where configurations instead of single HRM practices play a role.
Keywords: 650; configurations; convergence; energy distance; selection